Leading the quality initiative : implementing a business quality system (AT&T Quality Steering Committee [S.l.]US, 1991)
Examines the meaning and implications of creating value for customers, managing and improving processes, and empowering employees. Proposes an action plan for implementing the Quality Initiative. Activities include: involving staff in improvement activities and other quality-related efforts; tracking progress; and improving the quality system.
Bibliography: p.112-114. Located in the Learning Resource Centre.